Review on Research Methods for Studying Transition from Early Childhood Education to Primary Education - Alba González-Moreira; Camino Ferreira; Javier Vidal (MDPI AG, 2023)
The transition from early childhood to primary education is a process of changes that students undergo. Recent studies indicate that it is necessary to involve all actors in research: teachers, families, and students. Nevertheless, some researchers point to an "adult-centred" view, justified by the lack of linguistic communication among 5-7-year-olds. This study aims to describe the methods used in research on the transition from Early Childhood Education to Primary Education and to evaluate which methods support the participation of all actors involved. We conducted a systematic review of empirical studies between 2016 and 2021. The data show, on the one hand, that students of such a young age are not usually included in these studies. However, there has been an increase in studies that rely on students' opinions and perceptions. On the other hand, studies that include all actors involved in the transition are a minority. Students of such a young age are not usually included in these studies. When they are included, adapted information collection tools are used. Only by having the students and triangulating the information among all participants is it possible to provide complete information on the process. In addition, there is a lack of action research designs to offer comprehensive and practical improvement actions.